The values of family and social sources resilience of disability children: a phenomenology study - Sigit Muryono; Kadek Suranata (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
This study was Aimed to describe how the values of the family resilience of children with hearing loss in the Bengkala, Bali. The study of participants included the parents of children with hearing loss, and community in Bengkala, Bali, Indonesia. In this study, values are understood as a crucial concept to explain the underlying motivations of resilience attitudes and behaviors demonstrated by the members of the family of children with hearing impairment. The data analysis technique using coding that is open coding, axial coding and selective coding, There are three themes related to the values that underlie the family resilience of parents of the childrent with hearing impairment in Bengkala, the which include: (1) the value of tradition and religious; respect, commitment and acceptance of traditional cultural customs and ideas or religion given, (2) The value of the policy; the which is the value of keeping and giving happiness, prosperity with the people who Often interaction in their group and (3) the value of universalism; that is the value of understanding, appreciation, tolerance, and protection for the welfare of all people and the environment.